Effects of Inluin and Oligofructose Fortification on the Physico-Chemical, Sensory and Functional Properties of Clarfified Banana Juice - Yousaf, Muhammad Sohail (2006)
A comparative study conducted between Berangan and Mas banana cultivars at the same maturity index 6 (fully yellow-good eating stage) revealed that Berangan was more suitable for value added processing because of its lower soluble protein concentration, peroxidases and polyphenoloxidase activity. The two enzymes are responsible for developing browning in fruit tissues and also ultimately in the juice. Berangan has better sensory attributes in terms of taste, colour and over-all acceptability. Inulin and oligofructose are non-digestible oligosaccharides found in banana at 0.3-0.7%, respectively. These are considered too low to have any significant prebiotic effect for host health. Therefore clarified banana juice was prepared and fortified with inulin and oligofructose in order to increase its nutritional and functional properties. The fortification levels of inulin and oligofructose optimized at 2% and 10%, respectively yield banana juice with acceptable sensory and physical characteristics without effecting the original taste and flavour of banana. Storage study was conducted for 8 weeks at 4 0C, 25 0C and 35 0C to determine the storage stability of clarified banana juice fortified with inulin and oligofructose. The juice quality remained stable in terms of its physicochemical, microbiological and sensory characteristics for 8 weeks at different storage temperatures except for turbidity, whose continuous increase during storage in all the samples was found a critical quality problem especially for samples stored at 35 0C. However juice samples stored at 4 0C had less turbidity problem and were rated highest and most acceptable for different sensory parameters. The results of the in vivo study revealed that administration of fortified banana juice significantly increase the growth of health promoting bacteria i.e. Bifidobacterium and Lactobacillus, short chain fatty acids especially butyrate in the gut of the treated rats compared to rats fed distill water and with plain clarified banana juice. There was also an increase in mucosal thickness in cecum and proximal colon of rats fed with fortified juice, hence reduces the chances of many large bowel diseases. Rats of this same group also observed significant reduction in total cholesterol and LDL (Low density lipoprotein) concentration in the serum lipid thus contributing to hypochlesterolemic effect for patients with high serum cholesterol level.